Understanding and Implementing the Islamic Academic Culture of Unissula and the Tagline of Unissula in Sendangguwo, Semarang - Sholeh, Muhammad Muhtar Arifin; Nuridin, Nuridin (LPPM Universitas Islam Sultan Agung, 2023)
This study aims to socialize Budai (Islamic Academic Culture) and the tag-line of Unissula (Sultan Agung Islamic University) – namely BMGKU (Bismillah Building Generation of Khaira Ummah) to the community and to explore how community members understand and practice these things. From this socialization and deepening, the community is expected to be more familiar with Unissula's vision, mission, and goals, so that they are interested in loving Unissula and appreciating Unissula. The problem that arises in this service program is that people do not understand and practice the Unissula (BMGKU) and Budai taglines. The methods used in this program are lectures, questionnaires, and observation. The data collected is qualitative data which includes data on understanding and practice of